131J-speichernde pulmonale und ossäre Metastasen differenzierter Schilddrüsenkarzinome bei niedrigem Serum-Thyreoglobulinspiegel – Ausnahme in der Tumornachsorge? - Arning, G.; Ehrenheim, Ch.; Schober, O.; Hundeshagen, H. (Nuklearmedizin - NuclearMedicine, 1987)
In the follow-up of differentiated thyroid carcinoma it is discussed whether the tumormarker thyroglobulin can replace the1311 scan, especially when the thyroglobulin serum level is normal. A positive1311 scan of metastases in the follow-up of patients with differentiated thyroid carcinoma combined with a low serum thyroglobulin level is extremely rare. The literature shows a frequency of about 4%. Recently we found 3 cases with a positive1311 scan demonstrating pulmonary and bone metastases whereas the serum thyroglobulin level was low.